2004
DOI: 10.1038/ni1134
|View full text |Cite
|
Sign up to set email alerts
|

Distinct T cell dynamics in lymph nodes during the induction of tolerance and immunity

Abstract: Induction of immunity and peripheral tolerance requires contacts between antigen-bearing dendritic cells (DCs) and cognate T cells. Using real-time two-photon microscopy, we have analyzed the dynamics of CD8(+) T cells in lymph nodes during the induction of antigen-specific immunity or tolerance. At 15-20 h after the induction of immunity, T cells stopped moving and established prolonged interactions with DCs. In tolerogenic conditions, despite effective initial T cell activation and proliferation, naive T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
386
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(419 citation statements)
references
References 18 publications
31
386
0
2
Order By: Relevance
“…4B). In this scenario, DCs could be better described as tolerogenic than immunogenic cells [27]. A determination as to whether Tregs start Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4B). In this scenario, DCs could be better described as tolerogenic than immunogenic cells [27]. A determination as to whether Tregs start Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using these mice it will be possible to test the paradigm that upon entry into the tumor microenvironment from the periphery T cells become anergic, and subsequently to preclinically test strategies that are designed to reverse the signaling arrest of TIL and determine whether by reactivating these T cells the tumors are eradicated. The application of newer assay technologies such as two-photon laser-scanning microscopy will make it possible to visualize in tumor xenografts the dynamic changes in the movement, expansion, and contraction of lymphocytes, fibroblasts and tumor cells in vivo at the single cell level following perturbations to the tumor microenvironment that are designed to reactivate quiescent T cells [138,139]. A combination of fine needle biopsies and real time PCR will make it possible to monitor changes in gene expression patterns and alteration in tumor progression without sacrificing the xenograft bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…43 A recent study showed that individual long-lasting DC-T-cell interactions result in priming, whereas brief contact may contribute to the induction of T-cell tolerance. 51 It is likely that prolonged antigen-bearing DC survival may increase the chance or stability of DC-T-cell interactions during the induction of T-cell priming. Future studies need to be performed to determine whether: the transfection of DCs with Bcl-xl DNA change the level of expression of T-cell costimulatory molecules, MHC molecules, cytokines by the DCs or protect DCs from the Fas-mediated killing by freshly primed T cells; DC subsets are involved in T-cell priming; increased DC survival result in more DC-T-cell encounter, more prolonged DC-T-cell interactions, higher avidity of antigen-specific T cells, potent memory T-cell responses or improve chemokine-mediated T-cell trafficking in this self-antigen model.…”
Section: Discussionmentioning
confidence: 99%